2021
DOI: 10.1111/tri.14000
|View full text |Cite
|
Sign up to set email alerts
|

HCV eradication in recurrent hepatitis C after liver transplantation normalizes enhanced endothelial activation

Abstract: Summary The increased risk of cardiovascular disease (CVD) conferred by hepatitis C virus (HCV) is especially relevant after liver transplantation (LT), but its mechanism is still not well defined. This study aimed to evaluate the influence of HCV eradication in inflammatory and endothelial activation markers after LT. We evaluated inflammatory (TNF‐alfa, IL‐6, IL‐8, and MCP‐1) and endothelial activation (E‐selectin, ICAM‐1, VCAM‐1, and MMP‐9) markers before and after eradication in 45 LT recipients with HCV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…This correlation between HIV, HCV, and pro-inflammatory processes has very important clinical relevance, because it may be linked with the degree of liver fibrosis in HIV/HCV co-infected patients [13]. Recently, it has been shown that HCV eradication after effective treatment with direct acting antivirals (DAAs) or after liver transplantation diminished significantly, and even often normalized serum markers' levels of endothelial activation [14,15]. However, in HIV/HCV co-infected patients the situation is more complex, and even successful HCV eradication does not always lead to the normalization of systemic inflammation and endothelial dysfunction conditions, especially in persons with already-increased liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation between HIV, HCV, and pro-inflammatory processes has very important clinical relevance, because it may be linked with the degree of liver fibrosis in HIV/HCV co-infected patients [13]. Recently, it has been shown that HCV eradication after effective treatment with direct acting antivirals (DAAs) or after liver transplantation diminished significantly, and even often normalized serum markers' levels of endothelial activation [14,15]. However, in HIV/HCV co-infected patients the situation is more complex, and even successful HCV eradication does not always lead to the normalization of systemic inflammation and endothelial dysfunction conditions, especially in persons with already-increased liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%